Clinical assessment of implant‐supported full‐arch immediate prostheses over 6 months of function. (8th May 2019) - Shen, Huidan; Di, Ping; Luo, Jia; Lin, Ye
Abstract: Objective: To assess the clinical outcomes of implant‐supported full‐arch immediate prosthesis over 6 months of functions and analyze the risk factors of prosthetic complications. Materials and Methods: This retrospective cohort study included patients who were treated with implant‐supported full‐arch restoration under immediate loading protocol between April 2008 and June 2016, and who wore the immediate prosthesis for more than 6 months. Medical charts were reviewed for the patients' general information, implant information, prosthetic information, and details of any prosthetic complications. Prosthetic complications were classified as follows: class I, prosthesis loosening; class II, fewer than three artificial teeth fractured; class III, three or more artificial teeth fractured; and class IV, resin base fractures. A cox proportional hazards ratio model was adopted to analyze the potential risk factors for class IV complications. Results: A total of 114 patients (mean age, 56.73 ± 10.19 years) and 144 prostheses were included. The average wearing time for the immediate prosthesis was 21.9 months, and 62 (54.39%) patients experienced prosthetic complications, 30 of whom suffered from complications more than once. The most common complications were class II complications (12.3%) during the first 6 months of functioning and class IV complications (28.1%) during the entire function period. Class II complications were more common in the anterior region, while class IV complications occurred more often in the posterior region. The multivariable Cox proportional hazards regression model showed that a prosthesis in the maxilla (HR = 3.37, P = .001) and fiber reinforcement (HR = 0.39, P =  .021) were significantly related to class IV complications. Conclusions: Implant‐supported full‐arch immediate prosthesis functioning over 6 months have a high prevalence of prosthetic complications. Fiber‐reinforcement could reduce the prevalence of class IV complications when acrylic immediate prosthesis functioned longer than 6 months. Avoiding using the anterior teeth of the immediate prosthesis to tear pliable but strong food may prevent tooth fracture.